Clinical and Ultrasonographic Alterations in Canine Babesiosis - Mahima,; Mehta, HK; Bagherwal, RK; Chaurasia, R (Indian Journal of Veterinary Sciences and Biotechnology, 2020)
Canine babesiosis is a worldwide tick borne disease. Dogs with fever, in appetence and enlarged lymph nodes were screened for thepresence of haemoprotozoan parasites during the one year period of study at T.V.C.C., C.V.Sc., Mhow (M.P. , India ). Based on the stainedperipheral blood smears examination, dogs were found to be affected with babesiosis. Clinical examination of the dogs revealed ticksover the body, highest frequency (75.00%) of petechial/epistaxis followed by ticks (72.22%) on the body, recumbency (69.44%), dullness(66.66%), dehydration (63.88%), pale mucous membrane (50.00%) . Sonographic changes in dogs infected with babesiosis revealedhepatomegaly with architectural changes, hypo-echoic changes in the liver parenchyma in 7 dogs, splenomegaly with disturbedarchitecture and multiple lesions was observed in 9 dogs, cystitis in 5 dogs , distended gall bladder in 3 dogs and in 4 dogs Kidneysstructures were not clear in image and no demarcation noticed between cortex and medulla.
Keywords: Banesia; Canine; Ultrasonography